Analisis Konteks Wacana dan Tindak Tutur Pada Cerpen ‘Gubrak!' Karya Seno Gumira Ajidarma dalam Kajian Pragmatik - Siti Mawaddatul Fitriyyah; Diena San Fauziya (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The purpose of this research is to 1) find out and classify the context of the discourse on the Cerpen Gubrak! by Seno Gumira Ajidarma, 2) classification of submissions to each type, and 3) describe the mandate/massage of the meaning contained in the short story on students’ character education. This research uses qualitative descriptive research methods and data analysis techniques using literature study techniques, and data collection is by searching library sources (cerpen) from the internet, then reading and recording for data analysis purposes, then analysing research data. The results of the research on the Cerpen Gubrak! by Seno Gumira Ajidarma have implicit meanings so that researchers find meaning and respect that we can learn for everyday life as a form of appreciation and experience for both researchers and readers. Based on the results of the study, the researchers classified the analytical data found to each element and described the meaning contained in the context of the discourse. The results of the follow-up analysis data based on the above data are 2 locations, 3 illusions, and 5 perlocations.